2022
DOI: 10.1021/acs.jmedchem.2c00502
|View full text |Cite
|
Sign up to set email alerts
|

Design and Measurement of Drug Tissue Concentration Asymmetry and Tissue Exposure-Effect (Tissue PK-PD) Evaluation

Abstract: The "free drug hypothesis" assumes that, in the absence of transporters, the steady state free plasma concentrations equal to that at the site of action that elicit pharmacologic effects. While it is important to utilize the free drug hypothesis, exceptions exist that the free plasma exposures, either at C max , C trough , and C average , or at other time points, cannot represent the corresponding free tissue concentrations. This "drug concentration asymmetry" in both total and free form can influence drug dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 123 publications
(235 reference statements)
0
19
0
Order By: Relevance
“…From our comparative route of administration study, our data support the influence of tissue (pro)drug reservoirs incurred by route of administration. 16 This is most clearly demonstrated by the fate of the prodrug intermediate HemiPOMHEX after parenteral versus oral administration of POMHEX, in which intrahepatic levels of the latter likely explains the longer t 1/2 (Figure 2d). There are few reports on the influence of the intermediate metabolites of phosph(on)ate prodrugs such as TDF and TAF on the overall therapeutic activity of these prodrugs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…From our comparative route of administration study, our data support the influence of tissue (pro)drug reservoirs incurred by route of administration. 16 This is most clearly demonstrated by the fate of the prodrug intermediate HemiPOMHEX after parenteral versus oral administration of POMHEX, in which intrahepatic levels of the latter likely explains the longer t 1/2 (Figure 2d). There are few reports on the influence of the intermediate metabolites of phosph(on)ate prodrugs such as TDF and TAF on the overall therapeutic activity of these prodrugs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The marked divergence in pharmacokinetics between the parenteral and oral routes can be attributed to complex pharmacology of phosph­(on)­ate prodrugs, which are lipophilic when intact before being bioconverted to increasingly anionic metabolites. In contrast to metabolically inert drugs, this switch in physiochemical properties can result in intracellular trapping and the formation of tissue-specific drug reservoirs, which influences the half-life ( t 1/2 ) of the parent phosphonate due to slow systemic release over time . The influence of route of administration on the formation of tissue-specific drug reservoirs and t 1/2 of the parent pharmacophore has been made for separate phosphate prodrugsnamely remdesivir (administered IV) and sofosbuvir (administered PO). , Here we report the oral and parenteral pharmacokinetics for POMHEX; our data support the plausibility of the tissue reservoir hypothesis, which has been used to explain the long t 1/2 of the parent pharmacophores observed for this class of compounds.…”
mentioning
confidence: 99%
“…Moreover, 25c showed good bioavailability (90.52%) with a 10 mg/kg intraperitoneal administration. These high exposure and bioavailability suggested that 25c has the potential to inhibit JNK3 in vivo …”
Section: Resultsmentioning
confidence: 99%
“…49 Briefly, SH-SY5Y cells were incubated with DMSO (0.3% vol/vol) or 25c (30 μM) for 6 h. Then, cells were collected and resuspended in PBS. Following heating at the indicated temperatures (46,48,50,52,54,56,58, and 60 °C) for 3 min, cell suspensions were lysed by three freeze−thaw cycles with liquid nitrogen and thawed at room temperature. The lysates were separated by centrifugation at 17,000g for 20 min.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation